The effectiveness of promotional activities at KOWANESMA Berhad / Ernie Mohamad (Faculty of Business Management, 2007)
This project paper focuses on the use of promotional structures of marketing tools at Koperasi Warga Asli Negeri Sembilan dan Melaka Berhad (KOWANESMA). These tools include advertising, sales promotion and public relation. KOWANESMA Berhad uses such promotion tools to provide the information to customers and customers use them to obtain the information about the company. Therefore, the main objectives of the study are to identify the effectiveness of promotional activities at KOWANESMA Berhad to attract customers to purchase its products and services. Besides that, this study intends to identify the problems that the company facing and detect what kind of support that they need to become successful in their promotional activities. The objectives of this research are to identify the significant relationship between advertising, sales promotion and public relation and promotional effectiveness and to determine the strength of the company regarding its promotional activities. To ensure the success of this research, primary data collection method is applied. Primary data was gathered through 40 sets of questionnaires that had been distributed to the respondents, who are customers of KOWANESMA Berhad. SPSS program is being use in processing the data. The conclusions of this study are the outcome from the survey analysis, findings and recommendations given by the respondents. From the findings, it shows that public relation activity made by KOWANESMA Berhad is the major promotional activity that made the company get its customers compared to advertising and sales promotional activities. KOWANESMA Berhad has to improve its advertising and sales promotion activities, especially advertising. Finally, the researcher hopes that all data information and knowledge will be able to help KOWANESMA Berhad to identify its strength and weaknesses and be able to improve their promotional activities.